The Need for Establishing a New United Nations Body to Protect Earth from Back Contamination and Outer Space from Forward Contamination - Milanov, Aleksandar; Penchev, George (International Journal of Criminology and Sociology, 2022)
The purpose of the article is to explore the necessity to establish a new United Nations body, which is authorised to monitor and protect Earth and its organisms from biological contamination from extra-terrestrial sources and to protect outer space from forwarding contamination. Recent studies show that these contaminations could potentially have an extremely detrimental effecton life on Earth and for the safety of future outer space exploration. The study is doctrinal research and primary and secondary legal sources of international space law and environmental law are analysed. The research also applies a theoretical approach to determine what sets of principles should be applied and what intuitional innovation is needed to achieve optimally the goals of improving safety standards. This article presents a proposal for establishing a specialized UN organ to monitor an international agreement for the international planetary quarantine protocol of Earth. The need of establishing a new body in the system of the UN for protection of the Earth’s environment from harmful contamination caused by activities in outer space is quite distinguished. This publication aims also to increase awareness about the need for institutional innovation of the present UN system, particularly concerning global challenges like contamination from outer space and contamination of outer space. One of the major global challenges of today is the absence of safeguards for the protection of Earth from back contamination, an extra-terrestrial source of infection and destruction of space debris on the surface. The proposed new legal instrument would create guarantees for the protection of Earth and the outer space environment, support the adoption of a common space situational awareness system for monitoring and disclosing information about what is happening in outer space.